Geographies of violence and vulnerability - an actor-oriented analysis of the civil war in Sri Lanka - Bohle, Hans-Georg (ERDKUNDE, 2007)
The present paper views violence and vulnerability as social practice where human needs and human securities are constantly contested and fought over. It conceives the geographies of violence and vulnerability as arenas where human freedoms and rights are struggled for, negotiated, lost and won. In these struggles, however, the vulnerable are not mere victims, but they possess a lot of agency. They constantly try to cope with violent threats to their livelihoods, they deliberately adapt to the shifting regimes of violence, and they always seek to negotiate options that help to secure their livelihoods. The paper therefore employs an actor-oriented approach to violence and vulnerability. This approach is exemplified by two empirical case studies on particularly violent environments in eastern Sri Lanka during the civil war. The paper concludes by conceiving the geographies of violence and vulnerability as social spaces that have to be mapped according to the relative positions of the actors within dynamic fields of power.